2013
DOI: 10.1068/a45492
|View full text |Cite
|
Sign up to set email alerts
|

Back to the City: Internal Return Migration to Metropolitan Regions in Sweden

Abstract: Longitudinal microdata on the Swedish population, 1990-2006, are used to examine the numbers and characteristics of internal return migrants, emphasizing Sweden's three largest cities. Our study indicates that metropolitan regions are gaining population from net return migration, which thus carries people in the same direction as does most internal migration. Evidence also indicates that returnees to metropolitan regions are more likely to stay permanently than are migrants returning elsewhere. Furthermore, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
1
6
1
1
Order By: Relevance
“…Individuals who lived in more urbanised municipalities in 1995 are more likely to return: the probability of returning home is 13.7% higher for men from highly urbanised municipalities compared with men from nonurbanised municipalities. This result confirms the earlier results of Amcoff and Niedomysl (). To learn more about the background of return migrants to highly urbanised areas, an additional analysis was conducted.…”
Section: Return Migrationsupporting
confidence: 93%
“…Individuals who lived in more urbanised municipalities in 1995 are more likely to return: the probability of returning home is 13.7% higher for men from highly urbanised municipalities compared with men from nonurbanised municipalities. This result confirms the earlier results of Amcoff and Niedomysl (). To learn more about the background of return migrants to highly urbanised areas, an additional analysis was conducted.…”
Section: Return Migrationsupporting
confidence: 93%
“…Gender differences are reportedly marginal, but findings nonetheless indicate that men are more prone to return migration than are women (e.g. Newbold & Bell, ; Amcoff & Niedomysl, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…While counterurbanisation has traditionally been portrayed as lifestyle-induced migration, return migration is often understood based on a success-failure dichotomy, whereby the decision to return can be a result of failure (Haartsen & Thissen, 2014;Hunt, 2004). Amcoff and Niedomysl (2013) found that unemployment is a trigger for return migration in Sweden, both in general as well as specifically to metropolitan areas. In these terms, failure is often understood as economic failure, for instance unemployment.…”
Section: Return Migrationmentioning
confidence: 99%